Diversification of local products based on Wet Protein Isolate of Catfish (Clarias Sp) as a protein source to prevent stunting - Patmawati; Wini Trilaksani; Widati Fatmaningrum; Siti Rahayu Nadhiroh (Universitas Airlangga, 2022)
Stunting is a condition of failure to grow and develop in children due to lack of nutritional intake for a long time. This is a major threat in realizing quality Indonesian human resources. The consumption of animal protein in Indonesia is at least 6 kg/capita/day. Therefore, a food diversification program is needed to meet the needs of animal protein, especially those sourced from fish. One of the aquaculture commodities that has a very large opportunity to be developed in the context of fulfilling the nutrition of the Indonesian people is catfish. Therefore, the use of oversized catfish as an ingredient for the manufacture of local products in the form of cendol has the potential to be developed to increase protein content. This study aims to determine the formulation of a dessert (cendol) based on wet protein isolate (surimi) of catfish. The concentration of surimi used in the preliminary study was 0%, 10%, 20%, 30%, 40%, 50% and 60%. The resulting product is then characterized by organoleptic, chemical, and biological characteristics. The results of the proximate test in the main study showed that the higher the percentage of surimi used, the higher the protein content of cendol products. The results of the commercial cendol proximate test, and surimi-based cendol with the addition of 25%, 30%, and 35% surimi percentages were 1.24%, 4.13%, 4.74% and 5.47%, respectively. During 8 days of storage at 6oC there was a decline in product quality as seen from all test parameters on cendol products.